On the development of raem: The dutch spatial general equilibrium model and it's first application to a new railway link - Thijs Knaap; Jan Oosterhaven; Lóri Tavasszy (European Regional Science Association (ERSA), 2001)
This paper describes the development of a spatial computable general equilibrium model aimed at estimating the indirect economic effects of major transport infrastructure projects on Dutch regions. The RAEM model is based in the so-called new economic geography literature. It employs monopolistic competition for fourteen sectors as the basic market form, and calibrates most of its coefficients on recently constructed bi-regional input-output tables for the Netherlands. The general outline of the model is described and the way it fits in with evaluation schemes presently adopted by the Dutch government and the European Commission. A first version of the model has been applied to a base scenario for the year 2020 and has been used for evaluating the indirect economic effects of a new railway link between Amsterdam and Groningen. The paper describes the results of this exercise and discusses the way the RAEM model will be developed further in the near future.
Keywords: 330